An Overview of Smart Materials and Technologies for Concrete Construction in Cold Weather - Jonny Nilimaa; Vasiola Zhaka (Eng, 2023)
Cold weather conditions pose significant challenges to the performance and durability of concrete materials, construction processes, and structures. This paper aims to provide a comprehensive overview of the material-related challenges in cold weather concrete construction, including slow setting, reduced curing rate, and slower strength development, as well as frost damage, early freezing, and freeze–thaw actions. Various innovative materials and technologies may be implemented to address these challenges, such as optimizing the concrete mix proportions, chemical admixtures, supplementary cementitious materials, and advanced construction techniques. The paper also examines the impact of weather-related challenges for personnel, equipment, and machinery in cold environments and highlights the importance of effective planning, communication, and management strategies. Results indicate that the successful implementation of appropriate strategies can mitigate the challenges, reduce construction time, and enhance the performance, durability, and sustainability of concrete structures in cold and freezing temperatures. The paper emphasizes the importance of staying updated about the latest advancements and best practices in the field. Future trends include the development of smart and functional concrete materials, advanced manufacturing and construction techniques, integrated design, and optimization of tools, all with a strong focus on sustainability and resilience.